2001
DOI: 10.3928/0147-7447-20010401-15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hip Arthroscopy in the Evaluation of Avascular Necrosis

Abstract: This prospective study evaluated the correlation between plain radiographs, magnetic resonance imaging (MRI), and diagnostic arthroscopy in the staging of avascular necrosis of the femoral head. Fifty-two hips in 46 patients were prospectively staged using radiographic and MRI staging systems. Patients subsequently underwent hip arthroscopy to visualize the articular surface prior to considering salvage of the femoral head and debride delaminated osteochondral fragments. Weighted Kappa analysis revealed only m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ruch et al. presented poor correlation between radiographic and arthroscopic assessment of femoral head cartilage in patients with early post-collapse osteonecrosis, as arthroscopic evaluation revealed osteochondral lesions that had not been noted on radiograph or MR [ 56 , 57 ]. Mukisi-Mukaza et al.…”
Section: Histopathological and Microstructural Alterations Of Onfhmentioning
confidence: 99%
“…Ruch et al. presented poor correlation between radiographic and arthroscopic assessment of femoral head cartilage in patients with early post-collapse osteonecrosis, as arthroscopic evaluation revealed osteochondral lesions that had not been noted on radiograph or MR [ 56 , 57 ]. Mukisi-Mukaza et al.…”
Section: Histopathological and Microstructural Alterations Of Onfhmentioning
confidence: 99%
“…Furthermore, the time from pain onset to surgery was longer in femoral heads with articular surface irregularities than in those without such irregularities. Previous studies involving hip arthroscopy also showed articular cartilage degeneration in postcollapse ONFH that was not detectable on plain radiographs or MRI 10,11,42 . Therefore, earlier joint‐preserving surgery could be desirable because it can lead to satisfactory results, such as effectively preserving hip joints and preventing progression of subchondral collapse 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Severe subchondral collapse causes severe articular surface irregularities 8,9 . However, some necrotic femoral heads with radiological evidence of subchondral collapse have no gross abnormalities of the articular surface 10,11 . The degree of articular surface irregularities is expected to be related to the degree of subchondral collapse; however, there have been no reports evaluating this relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruch et al [46] reported on the use of arthroscopy of the hip in avascular necrosis and developed a staging classification for the feasibility of performing a revascularization procedure. Kloen [47] noted anterosuperior flattening of the femoral heads which reduced the head neck ratio leading to cam impingement.…”
Section: Discussionmentioning
confidence: 99%